Synthesis and characterization of CdS/PVA nanocomposite thin films from a complexing agent free system - Saikia, Dulen; Saikia, P. K.; Gogoi, P. K.; Das, M. R.; Sengupta, P.; Shelke, M. V. (Materials Chemistry and Physics, 2011)
CdS/PVA nanocomposite thin films have been deposited on glass substrates by in situ thermolysis of precursors dispersed in polyvinyl alcohol (PVA). The synthetic technique reported in this study is free from complexing agent and hence no need to control the pH of the solution as in the case of conventional CBD. The as-prepared films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED), UV-vis spectroscopy, and photoluminescence (PL) spectra. The XRD and SAED results indicated the formation of CdS nanoparticles with hexagonal phase in the PVA matrix. The photoluminescence and UV-vis spectroscopy revealed that CdS/PVA films showed quantum confinement effect. From the shift in optical band gap, particle sizes were calculated using effective mass approximation (EMA) method and it was found to be in agreement with the results obtained from TEM observations. The SEM results indicated that as grown films were homogeneous with no visible pinholes and cracks. The film prepared at 100 degrees C was found to be suitable for application as a window layer in solar cell. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CdS/PVA; Nanocomposite; Optical properties; Thermolysis

Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.